Policy Discourse on Restructuring Work Entry and Return Hours Based on Indicative Inquiry of the Jakarta Transportation Council - Hanafiah, Hally; Hadiansah, Ihsan; Yulian, Karina (FIRM Journal of Management Studies, 2023)
Recent data, observations and research show that the level of congestion at peak hours in Jakarta from mid-2022 to throughout 2023 has matched or even exceeded the level of congestion in 2019, or the time before the COVID-19 pandemic. One discourse to reduce the high level of congestion in DKI is the implementation of a policy to rearrange office hours in DKI and between May 22, 2023 and June 2, 2023 DTKJ conducted an indicative online questionnaire entitled "Survey on Rearrangement of Working Hours in DKI Jakarta" which covered 881 respondents. Based on the results of the indicative questionnaire, DTKJ recommended improvements to the public transport sector to be made by the DKI Jakarta Provincial Government, primarily by (i) increasing the public transport fleet, especially to operate during peak hours to reduce waiting time for users at public transport stops, terminals and stations, (ii) increasing the level of safety and comfort in the use of public transport, (iii) expanding service coverage areas to increasingly reach residential areas and suburban areas of DKI Jakarta, and (iv) increasing public transport service routes. The questionnaire results show that the majority, or more than 80 percent, of Jakarta transportation users approve of the implementation of rearranging work entry and return hours as a policy to reduce congestion levels, especially at peak hours. However, based on the results of the same online survey, DTJK concluded that the policy of rearranging work hours is not the main or only policy that can be carried out by the DKI Jakarta Provincial Government because improvements to the public transportation sector are the main steps that must be taken. In addition, the Jakarta Provincial Government is expected to ensure that the various policies that have been implemented can be enforced in the field and even expanded by continuing to review various policies that have the potential to reduce travel demand.